An ethnobotanical study of plants used in socio-religious activities in Bhutan (Asian Journal of Ethnobiology, 2022)
Abstract. Jigme, Yangchen K. 2022. An ethnobotanical study of plants used in socio-religious activities in Bhutan. Asian J Ethnobiol 5: 44-51. Ethnobotany encompasses all elements of plants’ natural and direct interaction with humans. Plants have been linked to human civilization since antiquity. Like Hindu people, Buddhists worship plants or use their components in different ways to perform various socio-religious ceremonies. However, this indigenous knowledge is diminishing rapidly due to the disinterest shown by the younger generation. Therefore, there need to document this indigenous knowledge regarding the usage of religious plants. The present study was conducted in Kanglung Gewog under Trashigang Dzongkhag, Bhutan, to document the plant species used for religious purposes. The ethnobotanical data were collected through semi-structured telephone interviews. A total of 24 plant species belonging to 16 families and 22 genera used in religious practices were documented. Among the 16 families, the most utilized species belong to the family Poaceae (4 species), followed by the family Ericaceae and Cupressaceae (3 species each) and Pinaceae (2 species). Out of these, trees account for 58 percent of all plants reported, followed by herbs (25%), shrubs (13%), and climbers (4%). The tree's trunk's most utilized parts, followed by the leaves, whole plant, seeds, and fruits. The majority of the plants recorded (58%) are used for religious ceremonies, and 42 percent of the plants are used for making religious items. The people of Kanglung have extensive indigenous knowledge on using plants in socio-religious activities. Still, rapid socio-economic development and the disinterest of the younger generation have become a major threat to preserving this indigenous knowledge. Therefore, it is necessary to preserve this indigenous knowledge on using plants in socio-religious activities by proper documentation and identification of plant species used to save these plants from further loss and sustainable utilization.
Keywords: Ethnobotany, indigenous knowledge, Kanglung, plants, rituals, socio-religious activities